(untitled) (Revista Venezolana de Salud Pública, 2018)
The World Health Organization emphasizes the need to generate knowledge about the health of women, however recognizes that there are still many gaps in the understanding of the particular challenges in that area faced by women and how these might be resolved effectively. In light of this, this study starts from the premise that doing research on the health status of women means assuming a different rationality, in the framework of a non-androcentric vision of knowledge. As such, it attempts to build a theoretical corpus to serve as onto-epistemological support the design of a research method with a gender perspective, able to explore both the subjective world as the target scenario-specific gender relations and their determinants of women’s health. It falls within the theoretical research mode of documentary, based on the deductive-dialectical. The argumentative confrontation led us reach a dialectical synthesis accounting theory based corpus, which foreshadows a final reflection on the method with feminist gender perspective which should be conceived as the dialectical unity between theory and practice, a theory that reflect critically on the concrete-symbolic nature of patriarchy as well as know how to define the complex set of procedures and techniques, the application will generate the necessary information, capable of being transformed and organized into a new understanding of the health status women.